1991
DOI: 10.1177/174114329101900304
|View full text |Cite
|
Sign up to set email alerts
|

An Experiment in Education Provision during Economic Hardship: A Third World Example

Abstract: In this paper the author reports on attempts in Trinidad and Tobago to implement a policy of universal secondary education in a project set up in 1988 and based ostensibly on a philosophy of education for all regardless of social class, political affiliation and economic circumstances during a period of economic hardship. From his perspective as a senior planner in the project, the author, who is currently at the University of Western Ontario, offers a penetrating critical examination of the political reasons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Despite a wide range of research methodologies and theoretical perspectives applied to research on secondary school principals presented in this journal, none have embraced Bourdieu’s arguments for the value of studies of strategies for getting to the heart of practice. While the terms rules (or regulations) and strategies occur in many articles, they are often used in plain language (London, 1991; Lumby, 2012; MacBeath, 2008; Marsh and LeFever, 2004; Moreland, 2009; Pansiri, 2011; Ranson, 2008), that is, not defined, explained or applied according to Bourdieu’s arguments in his theory of practice. Despite some researchers’ commitments to gaining access to the lived experiences of school leaders (Cliffe, 2011; Fuller, 2012; Ribbins, 1991; Russell, 2003; Smith, 2011; Starr, 2012), Bourdieu’s challenge to researchers to focus on strategies as a way of getting to the heart of practice has not been taken up by those researchers, nor in other research into secondary school leadership research reported in the Educational Management Administration and Leadership journal.…”
Section: Review Of Educational Management Administration and Leadership 1980–2013mentioning
confidence: 99%
“…Despite a wide range of research methodologies and theoretical perspectives applied to research on secondary school principals presented in this journal, none have embraced Bourdieu’s arguments for the value of studies of strategies for getting to the heart of practice. While the terms rules (or regulations) and strategies occur in many articles, they are often used in plain language (London, 1991; Lumby, 2012; MacBeath, 2008; Marsh and LeFever, 2004; Moreland, 2009; Pansiri, 2011; Ranson, 2008), that is, not defined, explained or applied according to Bourdieu’s arguments in his theory of practice. Despite some researchers’ commitments to gaining access to the lived experiences of school leaders (Cliffe, 2011; Fuller, 2012; Ribbins, 1991; Russell, 2003; Smith, 2011; Starr, 2012), Bourdieu’s challenge to researchers to focus on strategies as a way of getting to the heart of practice has not been taken up by those researchers, nor in other research into secondary school leadership research reported in the Educational Management Administration and Leadership journal.…”
Section: Review Of Educational Management Administration and Leadership 1980–2013mentioning
confidence: 99%